Forensic taphonomy of mass graves - Vaduvesković Igor; Đurić Marija (Medicinski Podmladak)
The archaeological context in mass graves, especially secondary ones (moved from the primary location), is much more complex due to the high fragmentation of the body. This complicates the process of exhumation, analysis and interpretation of the findings, and requires statistical data processing. The intensity of fragmentation of human remains differs between graves, depending on the formation processes of the grave and/or peri-mortem (at the time of death or near it) circumstances related to the individuals in it. This paper provides an overview of the methods of analyzing the taphonomic imprint of such processes on human remains, as well as the presentation of the process of degradation of the human body in the context of mass graves.